PERUBAHAN STRUKTUR MATA PENCAHARIAN MASYARAKAT NAGARI BANAI TENTANG PERGESERAN DARI SEKTOR PERTANIAN DAN PERKEBUNAN KE PENAMBANGAN EMAS - Raudatul Ilmi; Maulid Hariri Gani; Rini Sawitri (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to describe the changes in the livelihood structure of the Banai Nagari community, analyze the factors causing the shift from the agricultural and plantation sectors to the gold mining sector, and describe the impacts on the economic and social life of the community. This study uses a qualitative method with a descriptive approach. This study is based on the Theory of Social Change proposed by Soerjono Soekanto (2014), which explains that social change is a change in social institutions that influence the social system, values, attitudes and behavioral patterns of society due to the presence of internal and external driving factors that encourage adjustments to new conditions. Data collection was carried out through observation and interviews. Informants from this study consisted of village people, community leaders, farmers and planters who still farm and garden, former farmers and planters who turned into miners, mothers as cooks at gold mining sites, children of oil shunsir mining equipment and staple foods and other gold miners. The results of the study show that previously the agricultural and plantation sectors were the backbone of the economy with a percentage of 75-80% of the population in agriculture. However, in the past 5-7 years, a drastic shift has occurred, with more than 60% of the population now shifting their livelihoods to gold mining. The primary driver of this shift is the significantly larger and more immediate income disparity between mining and agriculture, while the agricultural and plantation sectors are dependent on weather conditions and lower selling prices. The resulting impacts include short-term improvements in economic well-being, but also the abandonment and destruction of agricultural land, the loss of interest in the agricultural and plantation sectors among the younger generation, and economic dependence on non-renewable natural resources.